Magnesium improved fruit quality by regulating photosynthetic nitrogen use efficiency, carbon–nitrogen metabolism, and anthocyanin biosynthesis in ‘Red Fuji’ apple - Tian, Ge; Qin, Hanhan; Liu, Chunling; Xing, Yue; Feng, Ziquan; Xu, Xinxiang; Liu, Jingquan; Lyu, Mengxue; Jiang, Han; Zhu, Zhanling; Jiang, Yuanmao; Ge, Shunfeng (Frontiers in Plant Science, 2023)
In order to solve the problems of low nitrogen utilization rate (NUE) and fruit quality degradation in apple production, we studied the effects of different application rate of magnesium (Mg) (0, 50, 100, 150, 200kg/ha) on the accumulation and distribution of carbon (C), nitrogen (N) metabolism, anthocyanin biosynthesis, and fruit quality of ‘Red Fuji’ apple in 2018 and 2019. The results showed that the application of Mg significantly increased the 15NUE and increased the allocation rate of 15N in the leaves, while the 15N allocation rate in the perennial organs and fruits were decreased. With the increase of Mg supply, the activities of N metabolism enzyme (NiR, GS and GOGAT) were significantly promoted, and the content of intermediate products in N metabolism (NO2-, NH4+ and free amino acid) was significantly decreased. Furthermore, an appropriate rate of Mg significantly promoted the net photosynthetic rate (Pn) and photosynthetic nitrogen use efficiency (PNUE), enhanced the enzyme activities of C metabolism (SS, SPS, S6PDH), and increased the contents of sorbitol and sucrose in leaves. Besides, Mg upregulated the gene expression of sugar transporter (MdSOT1, MdSOT3, MdSUT1 and MdSUT4) in fruit stalk and fruit fresh, 13C isotope tracer technology also showed that Mg significantly increased the 13C allocation in the fruits. Mg also significantly increased the expression of anthocyanin biosynthesis genes (MdCHS and MdF3H) and transcription factors (MdMYB1 and MdbZIP44) and the content of anthocyanin in apple peel. The comprehensive analysis showed that the appropriate application of Mg (150kg/ha) promoted PNUE, C-N metabolism and anthocyanin biosynthesis in apple trees.